Propuesta de diseño arquitectónico de un centro de acopio para productos agrícolas (El Triunfo - Patate) - Diaz Paucar, Bryan Alejandro (2026)
This paper proposed the architectural design of a primary agricultural collection and processing center in the El Triunfo parish, Patate canton. This initiative arose in response to the urgent need for adequate infrastructure that enables local farmers to efficiently store, process, and market their products, thereby improving the quality and competitiveness of agricultural production. Through a detailed analysis of the territory’s social, economic, and environmental conditions, several problems affecting the agricultural sector were identified, including a lack of modern equipment and dependence on primary production models with low added value. In this context, the proposed collection center seeks to overcome these limitations through a functional architectural design, designed to strengthen the value chain and boost the parish’s economic and social development. Beyond its technical function, the proposal aims to generate a positive impact on the community, promoting productive efficiency, equity, and the inclusion of producers in more competitive markets. In this sense, the project is presented as an alternative to boost the local economy and contribute to the well-being of the population, positioning the El Triunfo parish as a benchmark for agricultural development in the region.